2016
DOI: 10.1002/app.43611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of star‐shaped poly(alkyl methacrylate) arm uniformity on lubricant properties

Abstract: Star‐shaped poly(alkyl methacrylate)s (PAMAs) were prepared and blended into an additive‐free engine oil to assess the structure–property relationship between macromolecular structure and lubricant performance. These additives were designed with a comparable number of repeating units per arm and the number of arms was varied between 3 and 6. Well‐defined star‐shaped PAMAs were synthesized by atom transfer radical polymerization (ATRP) via a core‐first strategy from multi‐functional head‐groups. Observations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Star polymers are highly functional materials due to their compact, spatially defined, three-dimensional structure that leads to unique physical properties and increased opportunity for functionalization. They are currently used industrially as viscosity modifiers and lubricants, while potential applications in areas as varied as drug nanocarriers and interfacial stabilizers are also being investigated. Star polymers consist of linear arms that radiate from a central core and can be synthesized using a variety of controlled radical polymerization methods. Synthesis via reversible addition–fragmentation chain transfer (RAFT) polymerization has received significant attention and can be performed using either an arm-first or core-first approach .…”
mentioning
confidence: 99%
“…Star polymers are highly functional materials due to their compact, spatially defined, three-dimensional structure that leads to unique physical properties and increased opportunity for functionalization. They are currently used industrially as viscosity modifiers and lubricants, while potential applications in areas as varied as drug nanocarriers and interfacial stabilizers are also being investigated. Star polymers consist of linear arms that radiate from a central core and can be synthesized using a variety of controlled radical polymerization methods. Synthesis via reversible addition–fragmentation chain transfer (RAFT) polymerization has received significant attention and can be performed using either an arm-first or core-first approach .…”
mentioning
confidence: 99%
“…The tetra‐armed star‐shaped styrenic copolymers having pyrene side groups [ (S1‐S3)‐Pyr ] were prepared using core‐first approach (Scheme ), by which the number of arms of the star polymer could be clearly defined and would be equal to the number of the functional units on the polymerization‐initiating compound . Besides, this method provides good control on the macromolecular architecture .…”
Section: Resultsmentioning
confidence: 99%
“…To increase the resilience against shear-induced degradation, polymers with a branched architecture are preferred. The viability of this strategy has been verified both experimentally and by simulation studies, where polymers with varying architectures (linear, star, ring, H-, and comb-shaped) were subjected to high-shear conditions. , Although the presence of branch points enhances mechanical stability, they also introduce conformational constraints on the swelling behavior. The viscosity-improving performance of a given additive is, therefore, a trade-off between thickening efficiency and resilience against mechanical degradation or additive lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…recently developed polymeric additives combining bulk viscosity improvement with friction-reducing properties. The (hyper)­branched structures based on poly­(alkyl methacrylate) and poly­(ethylene) chemistries were evaluated, and the authors suggested the beneficial effect of branched architecture for (boundary) lubrication purposes. ,,, Particular attention was given to the incorporation of hydrophilic moieties into the polymer backbone to facilitate surface adsorption and formation of lubrication layers. However, the presence of hydrophilic fragments negatively impacted the bulk viscosity improving performance which can be attributed to a lower tendency to undergo temperature-induced swelling when dissolved in highly apolar base oils. , …”
Section: Introductionmentioning
confidence: 99%